PEMBERDAYAAN UMKM KOTA BATAM MELALUI DIGITALISASI PEMASARAN E-COMMERCE UNTUK PERTUMBUHAN EKONOMI - Effendi, Syahril; Tukino, Tukino; Harahap, Baru (LPPM Universitas Ibnu Sina, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth, particularly in Batam City, which serves as a key trade and industrial hub. Despite their potential, many MSMEs struggle with market expansion due to limited access and knowledge of digital marketing. This study aims to examine empowerment strategies for MSMEs through the digitalization of e-commerce marketing to enhance their competitiveness and economic contribution. The approach includes structured training, mentoring, and technical assistance to help MSMEs leverage e-commerce platforms, social media, and digital marketing techniques effectively. The training is conducted both in-person and online to ensure broad participation and maximize learning outcomes. Through this initiative, MSMEs are equipped with essential digital skills that enable them to reach a wider customer base, streamline operations, and boost revenue. Findings from this study indicate that digitalizing e-commerce marketing significantly enhances MSME visibility, operational efficiency, and financial performance. Key success factors include improving digital literacy among business owners, increasing government support, and fostering collaborations with e-commerce platforms. Addressing these factors ensures that MSMEs can successfully integrate into the digital economy and remain competitive in an increasingly technology-driven market. A sustainable digital transformation strategy is essential, emphasizing continuous digital skill development, access to necessary technological resources, and the establishment of a robust business ecosystem. By adopting e-commerce and digital marketing solutions, MSMEs in Batam City are expected to be more adaptable to market trends, strengthen their business competitiveness, and make a greater contribution to regional economic growth.